A retrospective population based cohort study of access to specialist palliative care in the last year of life: who is still missing out a decade on? - Rosenwax, Lorna; Spilsbury, Katrina; McNamara, Beverley; Semmens, James (2016)
Background: Historically, specialist palliative care has been accessed by a greater proportion of people dying with cancer compared to people with other life-limiting conditions. More recently, a variety of measures to improve access to palliative care for people dying from non-cancer conditions have been implemented. There are few rigorous population-based studies that document changes in palliative care service delivery relative to the number of patients who could benefit from such services. Method: A retrospective cohort study of the last year of life of persons with an underlying cause of death in 2009-10 from cancer, heart failure, renal failure, liver failure, chronic obstructive pulmonary disease, Alzheimer's disease, motor neurone disease, Parkinson's disease, Huntington's disease and/or HIV/AIDS. The proportion of decedents receiving specialist palliative care was compared to a 2000-02 cohort. Logistic regression models were used identify social and demographic factors associated with accessing specialist palliative care. Results: There were 12,817 deaths included into the cohort; 7166 (56 %) from cancer, 527 (4 %) from both cancer and non-cancer conditions and 5124 (40 %) from non-cancer conditions. Overall, 46.3 % of decedents received community and/or hospital based specialist palliative care; a 3.5 % (95 % CI 2.3-4.7) increase on specialist palliative care access reported ten years earlier. The majority (69 %; n?=?4928) of decedents with cancer accessed palliative care during the last year of life. Only 14 % (n?=?729) of decedents with non-cancer conditions accessed specialist palliative care, however, this represented a 6.1 % (95 % CI 4.9-7.3) increase on the specialist palliative care access reported for the same decedent group ten years earlier. Compared to decedents with heart failure, increased odds of palliative care access was observed for decedents with cancer (OR 10.5; 95 % CI 9.1-12.2), renal failure (OR 1.5; 95 % CI 1.3-1.9), liver failure (OR 2.3; 95 % CI 1.7-3.3) or motor neurone disease (OR 4.5; 95 % CI 3.1-6.6). Living in major cities, being female, having a partner and living in a private residence was associated with increased odds of access to specialist palliative care. CONCLUSION: There is small but significant increase in access to specialist palliative care services in Western Australia, specifically in patients dying with non-cancer conditions.